The Project Approach for Managing the Environmentally Oriented Development of the Regional Economy - Potravny, Ivan Mikhailovich; Yashalova, Natalya Nikolaevna; Gassiy, V.V.; Chavez, Ferreyra K. Y. (Economy of Regions, 2019)
In the article, we develop the project management methodology in the field of the environmental management and protection. The study’s relevance is due to the need to develop the principles and mechanisms of project management. They are necessary for implementing the economy’s environmentally oriented development, using the natural resources rationally, reducing the environmental burden and improving the quality of the population’s life. We aimed to substantiate the implementation of new management technologies by combining the principles of the project and ecological approaches, providing the flexibility of resource management. We suggested the differentiated approach in the project management in accordance with the strategic goals and achievement of the established indicators of the territory development. This approach ensures the project’s competitiveness, the possibility of its territorial geo-referencing, the efficiency of the project’s implementation. Further, we developed theoretical approaches and practical recommendations for implementing the project approach for managing the region’s environmentally oriented development. We incorporated the results of modern studies in developing the project management methodology in the regional economy. Moreover, we considered the preconditions of transitioning to project-oriented management in the sphere of the environmental management and protection. We identified characteristics of the ecologically oriented projects. Then we proposed their classification using the project’s functional purpose, the results’ purpose and direction, the project’s sources of financing and its implementation level as the classification criteria. We analysed the practical experience of implementing the environmental projects in the Russian Federation and in certain regions of the country. Finally, we demonstrated the advantages of the project approach in comparison with the program-target management of economic development. The study’s main provisions can be used as a theoretical, methodological and practical basis for substantiating, selecting and implementing the projects of environmental and economic orientation. They include the projects of production’s ecological modernization, reduction of negative environmental impact, elimination of accumulated ecological damage, management of climate changes, Arctic’s development, and development of the market of ecological goods and services.